Quantitative evaluation of HIV prevention programs - Kaplan, Edward Harris; Brookmeyer, Ron (Yale ISPS series., 2002)
How successful are HIV prevention programmes? Which HIV prevention programmes are most cost effective? Which programmes are worth expanding and which should be abandoned altogether? This book addresses the quantitative evaluation of HIV prevention programmes, assessing several different quantitative methods of evaluation.